Studies on strain sensitivity of Trichomonas vaginalis to metronidazole. Issue 2 (April 1978) - Meingassner, J G; Havelec, L; Mieth, H
Abstract : Ninety-four strains of Trichomonas vaginalis isolated from unselected patients in Vienna during the period from November 1975 to November 1975 were subjected to sensitivity tests against metronidazole in vitro and in vivo. Nearly 90% of the isolates examined showed in vitro growth inhibition at concentrations of 0.4 to 1.6 microgram metronidazole/ml and only about 10% at concentrations of less than 0.4 microgram/ml. All isolates showed some inhibition of growth after incubation for 48 hours with 3.2 microgram metroidazole/ml. Tests on treatment carried out on experimentally infected mice revealed that all strains of T. vaginalis examined were sensitive to metronidazole (MDE: less than 3 x 35 mg/kg peroral).